2022
DOI: 10.1038/s41598-022-06774-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind placebo-controlled clinical trial of oral hydroxyurea for transfusion-dependent β-thalassaemia

Abstract: Hydroxyurea is an antimetabolite drug that induces fetal haemoglobin in sickle cell disease. However, its clinical usefulness in β-thalassaemia is unproven. We conducted a randomised, double-blind, placebo-controlled clinical trial to evaluate the efficacy and safety of hydroxyurea in transfusion-dependent β-thalassaemia. Sixty patients were assigned 1:1 to oral hydroxyurea 10–20 mg/kg/day or placebo for 6 months by stratified block randomisation. Hydroxyurea treatment did not alter the blood transfusion volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In a phase 3 trial, adverse events experienced by patients with TD β-thalassemia treated with hydroxyurea for 6 months included headache (2 of 30 patients), thrombocytopenia (1 of 30), leukopenia (1 of 30), hyperpigmentation (1 of 30), urinary tract infection (2 of 30), nausea (1 of 30), vomiting (1 of 30), and abdominal pain (1 of 30). 37 The short-term safety profile of hydroxyurea appears to be favorable to luspatercept; however, the increases in hemoglobin are generally less than those for luspatercept 38 ; likewise, hydroxyurea benefit is not as durable. Furthermore, long-term randomized trials of hydroxyurea in β-thalassemia are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 3 trial, adverse events experienced by patients with TD β-thalassemia treated with hydroxyurea for 6 months included headache (2 of 30 patients), thrombocytopenia (1 of 30), leukopenia (1 of 30), hyperpigmentation (1 of 30), urinary tract infection (2 of 30), nausea (1 of 30), vomiting (1 of 30), and abdominal pain (1 of 30). 37 The short-term safety profile of hydroxyurea appears to be favorable to luspatercept; however, the increases in hemoglobin are generally less than those for luspatercept 38 ; likewise, hydroxyurea benefit is not as durable. Furthermore, long-term randomized trials of hydroxyurea in β-thalassemia are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that HU, despite the lack of specific approval for β-thalassemia and of robust clinical evidence 37 , is indeed used and provides sustained benefits in certain patients 38 . On the other hand, a substantial percentage of patients does not respond and some of the responding ones become insensitive after repeated administrations 39 , thus new interventions are eagerly needed.…”
Section: Drug Repositioning For Rare Diseases: β-Thalassemiamentioning
confidence: 99%
“…Supporting a caution in using multiplexed CRISPR-Cas9-based approaches, Samuelson et al recently reported that multiplex CRISPR-Cas9 genome editing in hematopoietic stem cells for fetal hemoglobin reinduction generates chromosomal translocations [ 40 ]. For these reasons, we therefore decided to use for HbF induction a repositioned drug, rapamycin [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], among those already validated and used in clinical trials [ 49 , 50 , 51 , 52 ]. To the best of our knowledge, this strategy is novel, as no study is available on the combination of pharmacological induction of HbF with gene editing procedures aimed at the de novo production of HbA following the CRISPR-Cas9-based correction of genetic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin, also known as sirolimus, is a potent inducer of HbF in in vitro systems [ 42 , 43 , 44 , 45 , 46 , 47 , 52 ], in in vivo animal models [ 46 , 47 , 53 , 54 ], and in few but highly informative patients affected by sickle-cell disease (SCD) [ 55 , 56 ]. In conclusion, all the available in vitro data concurrently indicate that rapamycin can be repurposed for the treatment of β-thalassemia for the following reasons: (a) rapamycin increases HbF in cultures from β-thalassemia patients with different basal HbF levels; (b) rapamycin increases the overall Hb content per cell; (c) rapamycin selectively induces γ-globin mRNA accumulation, with only minor effects on β-globin protein and β-globin mRNAs; (d) there is a strong correlation between the HbF increase induced by rapamycin and the increase in γ-globin mRNA content.…”
Section: Introductionmentioning
confidence: 99%